Physiological responses to hypoxic constant-load and high-intensity interval exercise sessions in healthy subjects - Chacaroun, S.; Vega-Escamilla y Gonzalez, I.; Flore, P.; Doutreleau, S.; Verges, Samuel (European journal of applied physiology, 2019)
Purpose The aim of this study was to assess the acute cardiorespiratory as well as muscle and cerebral tissue oxygenation responses to submaximal constant-load (CL) and high-intensity interval (HII) cycling exercise performed in normoxia and in hypoxia at similar intensity, reproducing whole-body endurance exercise training sessions as performed in sedentary and clinical populations. Methods Healthy subjects performed two CL (30 min, 75% of maximal heart rate, n = 12) and two HII (15 times 1-min high-intensity exercise—1-min passive recovery, n = 12) cycling exercise sessions in normoxia and in hypoxia [mean arterial oxygen saturation 76 ± 1% (clamped) during CL and 77 ± 5% (inspiratory oxygen fraction 0.135) during HII]. Cardiorespiratory and near-infrared spectroscopy parameters as well as the rate of perceived exertion were continuously recorded. Results Power output was 21 ± 11% and 15% (according to protocol design) lower in hypoxia compared to normoxia during CL and HII exercise sessions, respectively. Heart rate did not differ between normoxic and hypoxic exercise sessions, while minute ventilation was higher in hypoxia during HII exercise only (+ 13 ± 29%, p < 0.05). Quadriceps tissue saturation index did not differ significantly between normoxia and hypoxia (CL 60 ± 8% versus 59 ± 5%; HII 59 ± 10% versus 56 ± 9%; p > 0.05), while prefrontal cortex deoxygenation was significantly greater in hypoxia during both CL (66 ± 4% versus 56 ± 6%) and HII (58 ± 5% versus 55 ± 5%; p < 0.05) sessions. The rate of perceived exertion did not differ between normoxic and hypoxic CL (2.4 ± 1.7 versus 2.9 ± 1.8) and HII (6.9 ± 1.4 versus 7.5 ± 0.8) sessions ( p > 0.05). Conclusion This study indicates that at identical heart rate, reducing arterial oxygen saturation near 75% does not accentuate muscle deoxygenation during both CL and HII exercise sessions compared to normoxia. Hence, within these conditions, larger muscle hypoxic stress should not be expected.